Una nueva mirada a la estructura organizativa y operacional en enfermería (1999)
ABSTRACT: In this paper, the new approaches in management that organizations may face in order to fulfill user’s needs are presented as well as the importance in their implementation in nursing. In this way, an integral care of quality and equality to all users. At the same time, this is a point of reference and reflection on what nursing may be in changing world with deep crisis, based on their role in teamwork, research and human development as basic axes of effective change.